Influence of Copper Pretreatment on the Phase and Pore Formations in the Solid Phase Reactions of Copper with Tin - Morozovych, V.V.; Honda, A.R.; Lyashenko, Yu.O.; Korol, Ya.D.; Liashenko, O.Yu.; Cserhát, С.; Gusak, A.M. (Металлофизика и новейшие технологии, 2018)
The solid-phase reactions of copper with tin are considered, and the porosity of the reaction products depending on the pretreatment of the copper substrate is investigated. Copper substrates for the reaction are prepared by electrodeposition of copper layers with thickness of up to 100 microns on the rolled copper plates. The defects of substrates are determined by the different modes of electrodeposition—stationary, reversible, and stochastic ones. As shown, the thicknesses of the intermediate phases, their ratio, the number and spatial distribution of pores in the reaction products significantly depend on the mode of electrodeposition. The statistical dependences of the pore distribution along and across the interface as well as the characteristics of the roughness of the interface are revealed.